1969
DOI: 10.1542/peds.43.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Drug Testing in Children: Fda Regulations

Abstract: The testillg of drugs for use ill cilildren is difficult to accomplish, and it is even difficult to write about. Anything that smacks of "experimentation" on a child or even the use of a placebo given to a sick child is an emotionally charged subject. To carry out procedures that cannot be considered as essential to therapy, especially when they are painful or tiresome, seems abhorrent. However, it is recognized that the effects of many drugs on children may vary considerably from the effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In adults, the liver was identified as the target of APAP toxicity in the 1960s [ 6 - 8 ]. At that time, however, the view that babies metabolize drugs identically to adults was already known to be an unreliable and potentially dangerous assumption [ 9 ]; this knowledge had yet to be applied to the toxicity of APAP in children [ 5 ]. More than a decade later, a study using laboratory animals demonstrated that this assumption probably did not apply to APAP metabolism [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In adults, the liver was identified as the target of APAP toxicity in the 1960s [ 6 - 8 ]. At that time, however, the view that babies metabolize drugs identically to adults was already known to be an unreliable and potentially dangerous assumption [ 9 ]; this knowledge had yet to be applied to the toxicity of APAP in children [ 5 ]. More than a decade later, a study using laboratory animals demonstrated that this assumption probably did not apply to APAP metabolism [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in adults, the liver was found to be the target of acetaminophen toxicity during the 1960s (4)(5)(6). At that time, however, the view that babies metabolize drugs in a manner identical to adults was already known to be a dangerous assumption (7); this knowledge has yet to be applied to the toxicity of acetaminophen in human children (3). More than a decade later, a study using laboratory animals demonstrated that this assumption should not be applied to the metabolism of acetaminophen (8).…”
Section: Introduction: Mounting Evidence For the Induction Of Neurode...mentioning
confidence: 99%